Computer simulation of hydration of different structural forms of polyriboadenylic acid - Shestopalova, A. V. (Biophysical Bulletin, 2007)
Computer simulation of interaction of neutral single-stranded and protonated double-strand helical forms of polyriboadenylic acid (polyrA) with water environment has been carried out by Monte Carlo method. The energetic and structural characteristics were obtained and hydration scheme of all investigated structural components of polyrA were determined. The comparison with experimental results has been performed. It was shown that the additional stabilization of single and double stranded helical forms of polyrA may be realized in the result of ordered water structure formed in hydration shells of polyrA.